Design of Graphical User Interface Development Environment Software for sizing of Grid Connected Photovoltaic (GCPV) system - Z.Mohammad Noor, S; Zaini, S; M.Omar, A (International Journal of Engineering and Technology, 2018)
This work presents a design of graphical user interface development environment (GUIDE) software for sizing of Grid Connected Photovoltaic (GCPV) system. The simulation model of the GCPV system design is developed by using GUIDE in MATLAB. The developed GUI display the performance of the PV system based on the three scenarios. The three scenarios are sizing based on architecture constraint, the energy required and budget constraint. The size of the GCPV system is from 4.6 kW to 60.0 kW. A GUIDE is developed to design and calculate the suitable size of photovoltaic (PV) module, analyses the optimum array configuration, selection of inverter, size of cable, determine the specific yield and performance ratio. The GUI be able to make a userâ€™s job easier and beneficial in assisting the GCPV system design process compared to the manual calculation of the GCPV system.Â Â